Simulation study of cooling system for photovoltaic panel using ansys - Tahar, M. S. M.; Rosli, Nurrina (Penerbit UMP, 2022)
Photovoltaic or PV system are very important nowadays because of its functionality of absorbing energy of sunlight and convert it to electric energy. By applying the PV panel, it can cut the cost of billing for the users. It also called a green technology because it produces clean of the energy that can avoid from global warming and air pollutant. Despite of the benefits that it produces, the efficiency process of the system depends on how it been take care. The PV panel cannot be exposed to the high temperature of sunlight. If PV panel getting hot, the PV panel system cannot produce a full of its efficiency to user. By applying the cooling system on the PV panel, it can control and reduce the temperature of PV panel when the temperature increase. The simulation run was taken place in this research by using Ansys software. The result shows the reduction of the temperature of PV panel by applying mass flow rate of air and water. The inclination angle also plays a role in the simulation because if the angle of inclination of PV panel exposed more to sunlight it easily can make the PV panel hot. When the values of the mass flow rate increased, the lower the temperature of the PV panel can be achieved.